PENGEMBANGAN BAHAN AJAR INTERAKTIF DENGAN SCAFFOLDING METAKOGNITIF UNTUK KEMAMPUAN DAN DISPOSISI BERPIKIR REFLEKTIF MATEMATIS SISWA - Yusuf Badri; Hepsi Nindiasari; Abdul Fatah (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
The purpose of this study was to produce interactive mathematics teaching materials with metacognitive scaffolding for students' thinking and mathematical reflective dispositions. This interactive teaching material is made in exetable windows (exe) format. The use of teaching materials is flexible with exe format so that it can be used on Windows-based computers. Exe is a type of file used to install or install applications based on a Windows operating system. This research is motivated by the weakness of students 'metacognitive abilities, and the small amount of teaching materials to develop interactive teaching materials with the ability of metacognitive scaffolding aspects, students' thinking abilities and mathematical reflective dispositions. This study uses a research and development design that contains 10 potential steps and problems, combining data, product design, design validation, revision design, product testing, product revision, usage testing, product revision and mass production. The results showed that the general interactive teaching material with metacognitive scaffolding for the ability and disposition of mathematical reflective thinking students had a very good classification with a contribution of 87.5% for education experts and 85.7% for mathematicians looking at resources Introduction, eligibility, presentation , and language. While for multimedia experts have 70%. Based on the results of expert tests and limited trials conducted on 10 grade VIII junior high school students in one of the junior high schools in the attack district it is undeniably related to interactive teaching materials with metacognitive scaffolding for support and 6% mathematical reflective. Keywords:  Interactive Teaching Materials, Scaffolding, Metacognitive, Reflective Thinking, Mathematical Disposition